In the clearing [large type] - Dugoni, Robert (Dugoni, Robert. Tracy Crosswhite series., 2017)
"A former police academy classmate and protégé asks Tracy to help solve a cold case that involves the suspicious suicide of a Native American high school girl forty years earlier. But as Tracy probes one small town's memory and finds dark, well-concealed secrets hidden within the community's fabric, her own life may be endangered"--